Mortality and prognostic factors in idiopathic inflammatory myositis: a retrospective analysis of a large multicenter cohort of Spain - Nuño-Nuño, Laura; Joven, Beatriz Esther; Carreira, Patricia E.; Maldonado-Romero, Valentina; Larena-Grijalba, Carmen; Cubas, Irene Llorente; Tomero, Eva Gloria; Barbadillo-Mateos, María Carmen; De la Peña Lefebvre, Paloma García; Ruiz-Gutiérrez, Lucía; López-Robledillo, Juan Carlos; Moruno-Cruz, Henry; et al. (Rheumatology international, 2017)
The present study was undertaken to assess mortality, causes of death, and associated prognostic factors in a large cohort of patients diagnosed with idiopathic inflammatory myositis (IIM) from Spain. A retrospective longitudinal study was carried out in 467 consecutive patients with IIM, identified from 12 medical centers. Patients were classified as primary polymyositis, primary dermatomyositis (DM), overlap myositis, cancer-associated myositis (CAM), and juvenile idiopathic inflammatory myopathies. A total of 113 deaths occurred (24%) after a median follow-up time of 9.7 years. In the overall cohort, the 2-, 5-, and 10-year survival probabilities were 91.9, 86.7, and 77%, respectively. Main causes of death were infections and cancer (24% each). Multivariate model revealed that CAM (HR = 24.06), OM (HR = 12.00), DM (HR = 7.26), higher age at diagnosis (HR = 1.02), severe infections (HR = 3.66), interstitial lung disease (HR = 1.61), and baseline elevation of acute phase reactants (HR = 3.03) were associated with a worse prognosis, while edema of the hands (HR = 0.39), female gender (HR = 0.39), and longer disease duration (HR = 0.73) were associated with a better prognosis. The standardized mortality ratio was 1.56 (95% CI 1.28–1.87) compared to the Spanish general population. Our findings indicate that IIM has a high long-term mortality, with an excess of mortality compared to the Spanish population. A more aggressive therapy may be required in IIM patients presenting with poor predictive factors.